Surgical cordotomy helps psychosocial suffering. Issue Volume 12:Issue e2(2022) (31st August 2019) - Abdul-Razzak, Amane; Murray, Alison; Duplessis, Stephan
Abstract : A young woman was admitted to our palliative care unit with severe pain to her right hip and leg. Her pain was uncontrolled despite aggressive use of opioids, adjuvant pain medications and spinal analgesia. She experienced significant psychological and social distress, but engaging in therapies with our multidisciplinary team proved difficult. Surgical cordotomy was pursued, which improved the physical pain and allowed her to re-engage in social and familial roles and meaningful activities. This case gives context to discuss the complex interactions between physical pain and psychosocial suffering. It is challenging to determine the relative contributions of physical, psychological, existential and social suffering, and this case highlights the complex relationships between these domains. In this case, managing the physical pain by means of a surgical cordotomy allowed the patient the opportunity to address other domains of suffering.